Nitrificação e desnitrificação em situações críticas de substrato - Cao, Sandra Maria de Souza. (2018)
This work evaluated the effect of long periods with limited availability of substrate (ammonium) and oxygen in the nitrification process and the performance of a denitrifying system subjected to high nitrate loading in moving bed biofilm reactors (MBBR). Two nitrification reactors were operated in parallel and have undergone different ammonium and oxygen limiting conditions. Fast recovery of ammonium removal efficiency was observed after the successive disturbing periods. However, the absence of oxygen caused a more drastic effect in the nitrification process as compared to the ammonium limitation. Nitrifying activity gradually decreased after the continuous ammonium and oxygen limitation periods until reaching a constant minimum value, revealing the capacity of the biofilm microbial consortium in sustaining a minimum nitrifying activity. The study involving the denitrification process demonstrated that the MBBR system subjected to elevated nitrate loads (2.6 kgNO3-N/(m3 /d)) was capable of reaching complete denitrification, particularly under COD/N rations above 6. Conversely, for lower COD/N ratio, nitrite accumulation and possible inhibition took place, especially at higher influent nitrogen loading rates. The specific denitrifying activity was proportional to the influent nitrate load, reaching up to 60 mgNO3- N/(gSAV.h). Forma adicional Também disponível on-line.